Green preparation of covalently co-immobilized multienzymes on silica nanoparticles for clean production of reducing sugar from lignocellulosic biomass. (10th September 2021) - Lin, Yuanqing; Jin, Wenhui; Cai, Lixi; Liu, Xin; Qiu, Yue; Zhang, Guangya
Abstract: Multienzyme co-immobilization has garnered increasing interest in biomass conversion due to the green catalytic properties. However, the conventional strategies for covalent co-immobilization were complicated (including carrier preparation, enzyme purification, and immobilization process) and not clean enough (such as harsh reaction conditions, high reagent and water consumption, and toxic chemical input). Herein, a simple and green strategy was proposed to address these issues by the integration of elastin-like polypeptide (ELP)-mediated green biomimetic silicification and the spontaneous covalent bond formation of SpyCatcher/SpyTag (SC/ST) protein pair. In this strategy, the SC was genetically fused to ELP and the resulting SC-ELP (SCE) was purified by inverse transition cycling (ITC) method. The nanocarrier (SCE@SiO2 ) was prepared rapidly via one-step biomimetic silicification at neutral pH and room temperature under ambient pressure. The obtained nanocarriers could be directly used for covalent co-immobilization without additional surface functionalization and activation. The ST-tagged recombinant bi-enzyme xylanase-ST-lichenase (XSTL) covalently self-conjugated onto SCE@SiO2 through the SC and ST reaction, which eliminated the use of cross-linking reagents. Notably, target-specific immobilization from cell crude extracts with excellent activity recovery (over 90%) eliminated reagent- and time-consuming purification process. Furthermore, the co-immobilized XSTL showed very good reusabilities, which retained 83.9% (lichenase) and 81.4% (xylanase) of the original activities in the seventh cycle, respectively. XSTL could accelerate the production of fermentable sugars from renewable biomass polysaccharide. Overall, this unique ELP-mediated silicification-based Spy-assisted enzyme self-immobilization (ESSESI) offered great potentials towards multienzyme co-immobilization for diverse applications in a cleaner manner. Graphical abstract: A step-saving and eco-friendly strategy was developed to covalently co-immobilize multienzymes on SiO2 NPs for biomass saccharification. Image 1 Highlights: Functionalization- and activation-free silica NPs were prepared via a green biomineralization. NPs could target-specifically co-immobilize the recombinant bi-enzyme XSTL from E. coli cell crude extract. XSTL covalently bound onto NPs via SpyCatcher/SpyTag spontaneous reaction. The co-immobilized XSTL showed high activity retention (>90%). Production of fermentable sugars increased by about two folds using the bi-enzyme XSTL.